Analisis Pola Pengasuhan Orang Tua Terhadap Anak Usia Dini Di Laman Sahabat Keluarga - Ali, Musyafa; Hermawan, Risdianto; Nurul Istiqomah, Asrida (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2023)
Parents as the main caregiver have a very important role in the process of growth of Nanak, the reason the foster pattern given by parents to will determine the future of the child. Increasingly, the era of foster pattern that is done by people in the child is increasingly berfariasi, this can be seen in the safety of family companions provided by the Ministry of Education and Culture. In some occasions we may encounter some authors who share personal and field experiences related to foster patterns applied to early childhood. Ann Research conducted by researchers classified as research librarary research by collecting primary data and sekundere related to articles about parenting patterns that are contained on the Family Friends page. This research uses a qualitative approach, to interpret and explain the research object, which is an analysis of parents ' parenting pattern of early childhood in the Family friends page. The results of this research indicate that from articles written by parents on the Friends of the family page describes the parenting process that is recorded by parents in children. Where the caregiving is given to the children aims to optimize the child's growth and instill positive values in the child. In addition, some articles also explain the impact of the parenting process in children, both positive and negative impacts, so that this article can be one of the learning materials for parents in the care of children